PENGARUH STRUKTUR ASET, PROFITABILITAS, LIKUIDITAS DAN RISIKO BISNIS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI - DESY MARIANI; SURYANI SURYANI (Universitas Budi Luhur, 2021)
This study aims to examine the effect of Asset Structure, Profitability, Liquidity and Business Risk on Capital Structure in Manufacturing Companies in the Consumer Goods Industry Sector listed on the Indonesia Stock Exchange for the 2016-2020 period. The method used in this study is a quantitative method. The data used is secondary data obtained from financial reports published on www.idx.co.id. The population of this research is all manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the 2016-2020 period totaling 64 companies. The sampling technique in this study used purposive sampling method with a total sample of 38 companies. This study uses descriptive statistical analysis and multiple linear regression. The results showed that Liquidity had a negative and significant effect on Capital Structure, while Asset Structure, Profitability and Business Risk had no effect on Capital Structure.